Relationship Between Knowledge About Personal Protective Equipment (PPE) And Use Of Personal Protective Equipment (PPE) Among Chicken Coop Workers - Fitra Handika Hutama; Leili Setiawan Rosyid Leili; Nur Aini Fatimah; Heru Wahyudi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Poultry farm workers are exposed to various occupational hazards, including dust, ammonia, biological agents, and zoonotic pathogens, which increase the risk of occupational diseases and work-related injuries. The use of Personal Protective Equipment (PPE) is one of the primary preventive measures to reduce these risks. However, PPE compliance among poultry farm workers remains low, and inadequate knowledge regarding occupational hazards and the benefits of PPE may contribute to this behavior. Objective: To determine the relationship between knowledge regarding Personal Protective Equipment (PPE) and PPE use among poultry farm workers. Methods: This quantitative correlational study employed a cross-sectional design. The study involved all 62 poultry farm workers, and total sampling was applied. Knowledge regarding PPE was measured using a structured questionnaire, whereas PPE use was assessed through direct observation using an observation checklist. Descriptive statistics were used to summarize respondents' characteristics and study variables. The association between PPE knowledge and PPE use was analyzed using contingency table analysis at a significance level of α = 0.05. Results: Of the 62 respondents, 32 (51.6%) had poor knowledge regarding PPE, while 53 (85.5%) were observed not using PPE during work activities. Workers with good knowledge demonstrated a higher proportion of PPE use than those with sufficient or poor knowledge. Statistical analysis showed a significant association between knowledge regarding PPE and PPE use among poultry farm workers (p < 0.001). Conclusion: Knowledge regarding PPE was significantly associated with PPE use among poultry farm workers. Workers with better knowledge were more likely to use PPE than those with lower knowledge levels. Strengthening occupational health and safety education, together with workplace support for PPE availability and supervision, may improve PPE compliance and contribute to reducing occupational health risks among poultry farm workers..